2018 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2018
DOI: 10.1109/iros.2018.8593795
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Bayesian Eigenobjects: Combining Linear Subspace and Deep Network Methods for 3D Robot Vision

Abstract: We introduce Hybrid Bayesian Eigenobjects (HBEOs), a novel representation for 3D objects designed to allow a robot to jointly estimate the pose, class, and full 3D geometry of a novel object observed from a single viewpoint in a single practical framework. By combining both linear subspace methods and deep convolutional prediction, HBEOs efficiently learn nonlinear object representations without directly regressing into high-dimensional space. HBEOs also remove the onerous and generally impractical necessity o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Such a hybrid model where the deep learning is assisted by additional sensor sources like synthetic aperture radar (SAR) imagery and elevation like synthetic aperture radar (SAR) imagery and elevation is presented by [40]. In the context of 3D robot vision, [42] have shown that combining both linear subspace methods and deep convolutional prediction achieves improved performance along with several orders of magnitude faster runtime performance compared to the state of the art.…”
Section: Making Best Use Of Edge Computingmentioning
confidence: 99%
“…Such a hybrid model where the deep learning is assisted by additional sensor sources like synthetic aperture radar (SAR) imagery and elevation like synthetic aperture radar (SAR) imagery and elevation is presented by [40]. In the context of 3D robot vision, [42] have shown that combining both linear subspace methods and deep convolutional prediction achieves improved performance along with several orders of magnitude faster runtime performance compared to the state of the art.…”
Section: Making Best Use Of Edge Computingmentioning
confidence: 99%
“…Bayesian Eigenobjects (BEOs) [3], [17] offer compact representations of objects. Using 3D object models for training, BEOs generate a low-dimensional subspace serving as a basis which well captures the object classes used to train it.…”
Section: Background and Related Workmentioning
confidence: 99%
“…This makes the BEO subspace a compelling target for language mapping in a robotics domain. Critically, the hybrid variant of BEOs (HBEOs) [17] learn an explicit subspace like BEOs, but use a deep convolutional network to learn an embedding directly from a depth image into the object-subspace, allowing for high performance, fast runtime, and the ability to complete objects without requiring voxelization of observed objects.…”
Section: Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations